Characterizing of intra-amniotic inflammatory changes associated with chronic inflammation in the placenta marked by elevated amniotic fluid interferon gamma-induced protein 10 (IP-10) in pregnancies complicated by preterm prelabor rupture of membranes - Aberšek, Nina; Tsiartas, Panagiotis; Soucek, Ondrej; Andrys, Ctirad; Musilova, Ivana; Jacobsson, Bo; Kacerovsky, Marian (European journal of obstetrics, gynecology, and reproductive biology, 2024)
OBJECTIVES: This study aimed to determine the occurrence of intra-amniotic inflammatory changes associated with chronic inflammation in the placenta, marked by elevated levels of interferon gamma-induced protein 10 (IP-10) (≥2200 pg/mL) in the amniotic fluid of women with preterm prelabor rupture of membranes (PPROM). Specifically, the study investigated whether these intra-amniotic inflammatory changes were more common in women with microbial invasion of amniotic cavity (MIAC) and intra-amniotic inflammation (IAI), as indicated by increased amniotic fluid interleukin (IL)-6 concentration (≥3000 pg/mL). STUDY DESIGN: A cohort of 114 women with singleton pregnancies complicated by PPROM between 24+0 and 36+6 weeks of gestation were included. Amniotic fluid samples were obtained via amniocentesis upon admission. MIAC diagnosis involved aerobic and anaerobic cultures, as well as polymerase chain reaction (PCR) analysis of the amniotic fluid. Immunoassay tests and enzyme-linked immunosorbent assay (ELISA) were used to determine IL-6 and IP-10 concentrations, respectively. RESULTS: Among the participants, 19.3 % and 15.8 % had MIAC and IAI, respectively. The occurrence of intra-amniotic inflammatory changes associated with chronic inflammation in the placenta was similar between women with and without MIAC (25 % vs. 40.9 %, p = 0.136, adjusted p = 0.213). The rate of intra-amniotic inflammatory changes associated with chronic inflammation in the placenta was significantly higher in women with IAI compared to those without, after adjusting for gestational age at sampling (55.6 % vs. 22.9 %, p = 0.005, adjusted p = 0.011). CONCLUSION: This study revealed comparable rates of intra-amniotic inflammatory changes associated with chronic inflammation in the placenta in women with and without MIAC, but a higher prevalence of intra-amniotic inflammatory changes associated with chronic inflammation in the placenta in women with IAI. These findings suggest involvement of chronic inflammation even in women with PPROM with acute intra-amniotic inflammation.
Keywords: novorozenec; Infant, Newborn; Intra-amniotic inflammation; Pregnancy; Humans; Interferon gamma-induced protein 10; Chemokine CXCL10; Placenta; Fetal Membranes, Premature Rupture; IP-10; gestační stáří; Female; Inflammation; lidé; chorioamnionitida; PPROM; zánět; Amniotic Fluid; IAI; Gestational Age; ženské pohlaví; plodová voda; MIAC; těhotenství; Chorioamnionitis; interferon gama; Microbial invasion of the amniotic cavity; placenta; předčasný odtok plodové vody; chemokin CXCL10; Interferon-gamma